2021
DOI: 10.3847/1538-4357/abe766
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Large-scale Magnetic Fields on the Model for Repeating Changing-look AGNs

Abstract: Periodic outbursts are observed in several changing-look (CL) active galactic nuclei (AGNs). Sniegowska et al. suggested a model to explain the repeating CL in these AGNs, where the periodic outbursts are triggered in a narrow unstable zone between an inner advection-dominated accretion flow and outer thin disk. In this work, we intend to investigate the effects of large-scale magnetic fields on the limit cycle behaviors of CL AGNs. The winds driven by magnetic fields can significantly change the structure of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Assuming a BH mass of 10 7 M ⊙ with Eddington-limited accretion rate m Edd = 1 and inner radius R 0 = 3R g , we estimate the value of τ fill to be ≳ 56 months even for a small truncation radius of 4 R g with α = 0.1, which is much longer than the observed duration (≲ 3 months) of the faint state for J0456−20. This timescale can be significantly shortened as in a toy model developed by Sniegowska et al (2020) (see also Pan et al 2021), in which the radiation pressure instability only operates in a narrow ring between a thin outer disk and an optically thin hot inner ADAF. However, our X-ray spectral analysis suggests that the temperature of the inner-region of the multi-colour disk does not change at different X-ray flux states.…”
Section: Other Potential Scenariosmentioning
confidence: 99%
“…Assuming a BH mass of 10 7 M ⊙ with Eddington-limited accretion rate m Edd = 1 and inner radius R 0 = 3R g , we estimate the value of τ fill to be ≳ 56 months even for a small truncation radius of 4 R g with α = 0.1, which is much longer than the observed duration (≲ 3 months) of the faint state for J0456−20. This timescale can be significantly shortened as in a toy model developed by Sniegowska et al (2020) (see also Pan et al 2021), in which the radiation pressure instability only operates in a narrow ring between a thin outer disk and an optically thin hot inner ADAF. However, our X-ray spectral analysis suggests that the temperature of the inner-region of the multi-colour disk does not change at different X-ray flux states.…”
Section: Other Potential Scenariosmentioning
confidence: 99%
“…Śniegowska et al (2020) proposed a simple time-dependent toy model of an accretion disk under radiation pressure instability, in which the timescale of the outbursts was regulated by the thickness of the unstable zone. Pan et al (2021) presented an extension of the Śniegowska et al (2020) model by adding a magnetic field and showed that the timescale of the outbursts can be significantly reduced by the magnetic fields. The possibility of shortening the timescales in CL AGN phenomena by magnetization of the accretion disk was also suggested by Dexter & Begelman (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, large spectral state changes in quasars challenge and invigorate debates about both accretion theory and the nature of historical quasar classes (i.e., type 1 versus type 2; Elitzur et al 2014). Some recent studies suggest that the timescale problem can be qualitatively alleviated when taking the large-scale magnetic field into account (Dexter & Begelman 2019;Pan et al 2021) or considering accretion disk instabilities (e.g., the radiation pressure instability; Sniegowska et al 2020).…”
Section: Introductionmentioning
confidence: 99%